Factors Affecting Capital Expenditure In Districts in West Java Province - Kholida Atiyatul Maula; Kartika Nur Alfiyah; Isro'iyatul Mubarokah; Wiwiek Rabiatul Adawiyah; Christina Tri Setyorini (Universitas Negeri Semarang, 2023)
Purpose: This study examines and analyzes the effect of Original Local Own Revenue (PAD), General Allocation Fund (DAU), Special Allocation Fund (DAK), Revenue Sharing Funds (DBH), and Excess Budget Financing (SiLPA) on Capital Expenditures. Method: This study employed a quantitative research design. The study's population consisted of all 27 West Java Province Districts, including 9 cities and 18 regencies. With a total sample of 135 district budget realization reports data in the province of West Java, the sample size for this study was determined using a census sampling approach. Findings: The findings show a positive effect of PAD and DAU on Capital Expenditure, indicating that the amount of realized Capital Expenditure depends on the amount of PAD and DAU obtained by Districts in West Java Province. Meanwhile, DAK, DBH, and SiLPA do not affect the realization of Capital Expenditures. This indicates that the realization of capital expenditure is independent of DAK, DBH, and SiLPA. Novelty: First, this study uses a different research paradigm than before. Second, this research utilizes the latest era to vary the independent variables. Third, the problems chosen in this study are regencies and cities in West Java Province, which need attention regarding capital expenditure allocation. Keywords: Capital Expenditures, Original Local Own Revenue, Balance Funds, Excess Budget Financing